PERSPEKTIF AL-QUR’AN TENTANG UJARAN KEBENCIAN DI MEDIA SOSIAL: Studi Analisis Terhadap Penafsiran Ayat-Ayat Etika Sosial - Saubatul Ramdlanah; Ulya Fikriyati (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract Social media is not solely a tool for communication and sharing positive information. Instead, platforms such as Facebook, WhatsApp, and Instagram have become breeding grounds for hate speech. The Qur'an promotes the creation of a harmonious social environment rather than one of hatred. This article explores the Qur'an's role in building morals, strengthening faith, and fostering brotherhood. Secondly, hate speech on social media poses a danger to the principle of Unity in Diversity in Indonesia. Thirdly, hate speech on social media is considered to be contrary to Pancasila, which emphasises unity. This research adopts a library research methodology using an interpretative sociological approach. The material is presented using a thematic systematics approach combined with Travis Hirschi's social control theory analysis. The research draws the following conclusions: Firstly, the Qur'an prohibits all forms of hate speech on social media that cause harm and loss to oneself, others, and society. Secondly, hate speech on social media has various implications, including psychological, political, economic, educational, and health aspects. Thirdly, provocative elements in hate speech on social media cause divisions in society. Keywords: Qiyâm al-Laîl, Tafsir Ahkam, and Tafsir Sufi